Hungary : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that although economic growth of Hungary slowed in 2001, the economy showed considerable resilience to the weaker external environment. GDP growth was a still respectable 3.8 percent, down from 5.2 percent in 2000 but higher than most other countries in the region. Although export growth decelerated as the year progressed, it nevertheless outpaced growth in Hungary's export markets. Domestic demand was partly supported by buoyant private consumption on the back of strong real wage gains. Meanwhile, the unemployment rate edged down to 5.6 percent by the start of 2002.